Factors impacting employee productivity in the UAE public sector embracing the Fourth Industrial Revolution - Khalifa Al-Suwaidi; Imad Alsyouf; Zain Tahboub; Abdallah Alsaad; Adi Alsyouf (Social Sciences and Humanities Open)
The Fourth Industrial Revolution (4IR) is rapidly transforming the nature of work, service delivery, and performance expectations in public sector institutions. These digital disruptions have raised critical questions about how employee productivity can be sustained amid evolving technologies and organizational structures. In this context, understanding the influence of human resource management (HRM), workforce capacity (WFC), and people leadership (PL) becomes essential for enhancing public sector performance. Grounded in socio-technical systems (STS) theory, this study proposes an integrated framework to address productivity challenges unique to the UAE context. A cross-sectional survey of 303 public-sector employees in Sharjah was conducted, and data were analyzed using descriptive statistics, inferential tests, and the relative importance index (RII) technique. The findings reveal that HRM, WFC, and PL significantly affect four key outcomes: productivity, quality of work life, distributive fairness (DF), and work-from-home arrangements (WHA). Notably, the most influential factor across all domains was a positive work environment (RII = 0.902), followed by job security (RII = 0.894) and supervisory behavior (RII = 0.889). These results provide empirical support for prioritizing human-centric strategies within public sector reform efforts. The study contributes to both theory and practice by offering evidence-based insights for policymakers aiming to strengthen workforce performance in the era of digital transformation.